MYD88 L265P mutation and interleukin‐10 detection in cerebrospinal fluid are highly specific discriminating markers in patients with primary central nervous system lymphoma: results from a prospective study. (23rd February 2021) - Ferreri, Andrés J. M.; Calimeri, Teresa; Lopedote, Paolo; Francaviglia, Ilaria; Daverio, Rita; Iacona, Chiara; Belloni, Cristina; Steffanoni, Sara; Gulino, Alessandro; Anghileri, Elena; Diffidenti, Angelo; Finardi, Annamaria; et al.
Summary: Reliable biomarkers are needed to avoid diagnostic delay and its devastating effects in patients with primary central nervous system (CNS) lymphoma (PCNSL). We analysed the discriminating sensitivity and specificity of myeloid differentiation primary response (88) ( MYD88 ) L265P mutation (mut‐ MYD88 ) and interleukin‐10 (IL‐10) in cerebrospinal fluid (CSF) of both patients with newly diagnosed ( n = 36) and relapsed ( n = 27) PCNSL and 162 controls (118 CNS disorders and 44 extra‐CNS lymphomas). The concordance of MYD88 mutational status between tumour tissue and CSF sample and the source of ILs in PCNSL tissues were also investigated. Mut‐ MYD88 was assessed by TaqMan‐based polymerase chain reaction. IL‐6 and IL‐10 messenger RNA (mRNA) was assessed on PCNSL biopsies using RNAscope technology. IL levels in CSF were assessed by enzyme‐linked immunosorbent assay. Mut‐ MYD88 was detected in 15/17 (88%) PCNSL biopsies, with an 82% concordance in paired tissue‐CSF samples. IL‐10 mRNA was detected in lymphomatous B cells in most PCNSL; expression of IL‐6 transcripts was negligible. In CSF samples, mut‐ MYD88 and high IL‐10 levels were detected, respectively, in 72% and 88% of patients with newly diagnosed PCNSL and in 1% of controls; conversely, IL‐6 showed a low discriminating sensitivity and specificity. Combined analysis of MYD88 and IL‐10 exhibits a sensitivity and specificity to distinguish PCNSL of 94% and 98% respectively. Similar figures were recorded in patients with relapsed PCNSL. In conclusion, high detection rates of mut‐ MYD88 and IL‐10 in CSF reflect, respectively, the MYD88 mutational status and synthesis of this IL in PCNSL tissue. These biomarkers exhibit a very high sensitivity and specificity in detecting PCNSL both at initial diagnosis and relapse. Implications of these findings in patients with lesions unsuitable for biopsy deserve to be investigated.